BEYOND THE LYRICS: IDENTITY CONSTRUCTION IN ROCKET ROCKERS' SONGS : An analysis of song lyrics by using Critical Discourse Analysis - Ramdhani, Imman (2012)
The present study entitled Beyond the Lyrics: Identity Construction in Rocket Rockers' Songs (An analysis of Song Lyrics by using Critical Discourse Analysis) aims to reveal identity of the band Rocket Rockers by applying Fairclough's framework of Critical Discourse Analysis and Halliday's Functional Grammar as the tools of the study. The focuses in this study are modality, evaluation and personal pronoun applied in the nine song lyrics collected from three Rocket Rockers album. The findings and discussion show that the band comes up with two different identity namely personal identity and social identity. Personal identity comes up with the issue of personal life while social identity comes up with the social issue that appeared in the society.